Rac1 and Stathmin but Not EB1 Are Required for Invasion of Breast Cancer Cells in Response to IGF-I - Shigeru Morimura; Kazuhide Takahashi (International Journal of Cell Biology)
Cell migration is considered necessary for the invasion that accompanies the directional formation of the cellular protrusions termed lamellipodia. In invasive breast cancer MDA-MB-231 cells, lamellipodia formation is preceded by translocation of the actin cytoskeletal regulatory protein WAVE2 to the leading edge. WAVE2 translocation and lamellipodia formation require many signaling molecules, including PI3K, Rac1, Pak1, IRSp53, stathmin, and EB1, but whether these molecules are necessary for invasion remains unclear. In noninvasive breast cancer MCF7 cells, no lamellipodia were induced by IGF-I, whereas in MDA-MB-231 cells, Rac1, stathmin, and EB1 were overexpressed. Depletion of Rac1 or stathmin by small interfering RNA abrogated the IGF-I-induced invasion of MDA-MB-231 cells; however, depletion of EB1 did not, indicating the necessity of Rac1 and stathmin but not EB1 for invasion. The signaling pathway leading to cell invasion may not be identical but shares some common molecules, leading to cell migration through lamellipodia formation.